Multivariate Analysis of Personal Hygiene, Residential Density, Socioeconomic Status, and Knowledge Toward Scabies Prevalence At the Serang City Islamic Boarding School - Trasia, Reqgi First; Faruqi, Azzam; Winita, Rawina; Muhammad Tola, Sakura; Keumala Dewi, Intan (UNUSA Press, 2024)
Introduction: Scabies is an infectious disease of the skin caused by the mite Sarcoptes scabiei var. hominis. This disease is often ignored because it is not life-threatening, but the itching that occurs can interfere with daily life. Scabies is often found in densely populated environments such as Islamic boarding schools, places where students study. Borrowing each other's personal items, living in rooms with high occupancy rates, and having poor habits regarding personal hygiene are risk factors for contracting scabies among students. Objective: Through this background, this research aims to determine the relationship between the level of personal hygiene, housing density, socioeconomic status, and the level of knowledge about scabies among students at the Islamic Boarding School, Serang, Banten. Methods: The research was carried out at the Islamic Boarding School, Serang, Banten with a sample size of 167 respondents. The research design used was a cross-sectional analytical design with a sampling technique using the simple random sampling method. Univariate analysis was carried out by assessing frequencies and percentages. Bivariate analysis of variables was carried out using the chi-square test. Multivariate analysis was performed using multiple linear regression. Results: Respondents in this study totaled 167 respondents. The results of the analysis show that the prevalence of scabies in Islamic boarding schools in Serang City is 47.3%. There is no significant relationship between personal hygiene and scabies prevalence (P = 0.603), and there is a significant relationship between housing density (P = 0.018), socioeconomic status (P = 0.002), and level of knowledge (P = 0.035) on scabies prevalence. at the Serang City Islamic Boarding School. Based on multivariate analysis, a relationship was found between residential density, socioeconomic status, and level of knowledge on scabies prevalence simultaneously. Conclusions: These research results show that factors such as housing density, socioeconomic status, and level of knowledge play an important role in the spread of scabies in Islamic boarding schools even though the students show good results in personal hygiene.